Toward a critical grounded theory. (14th November 2016) - Hense, Cherry; McFerran, Katrina Skewes
Abstract : Purpose: Research literature presents lively debate about whether research approaches traditionally belonging to distinct paradigms can be combined (Creswell, 2011). While much of this discourse has focussed on mixed methods studies that combine quantitative and qualitative data (Morgan, 2007), there has been less discussion of the implications and benefits of combining different approaches from two "alternative" paradigms. The purpose of this paper is to discuss the confluence of constructivist grounded theory as detailed by Charmaz (2006, 2011, 2014) with participatory research. Design/methodology/approach: The authors discuss points of tension and convergence between the constructivist and participatory paradigms that underpin these approaches, and consider how the differences might be reconciled through a notion such as critical grounded theory. The authors illustrate these points through examples from the research practice in youth mental health. Findings: The authors propose that incorporating some of the critical aspects of participatory philosophy into constructivist grounded theory offers a useful strategy for generating local theory in mental health research informed by social action agendas. Originality/value: This paper extends thinking in the field of participatory and grounded theory research and offers new concept for researchers engaging in critical inquiry.